The pCONus device in treatment of wide-necked aneurysms: technical and midterm clinical and angiographic results - Ulfert, Christian; Pfaff, Johannes; Schönenberger, Silvia; Bösel, Julian; Herweh, Christian; Pham, Mirko; Bendszus, Martin; Möhlenbruch, Markus Alfred (Clinical neuroradiology, 2018)
A variety of devices for treatment of wide-necked bifurcation aneurysms are emerging. Here we report our results using the new pCONus device with special emphasis on the morphological and anatomical requirements for successful implantation.
Published online: 16 September 2016
Gesehen am 19.02.2020